With or without force? European public opinion on democracy promotion - Jörg Faust; Maria Melody Garcia (Deutsches Institut für Entwicklungspolitik (DIE), 2013)
Against the background of the ongoing debate around European democracy promotion, we investigate the impact of European citizens' socio-economic backgrounds, political orientations and countries of origin on their support for democracy promotion in general and on democracy promotion via military means. Analysing survey data from 11 European Union (EU) member countries, we show that citizens with more extreme political orientations are less likely to support general democracy promotion. In contrast, particularly those citizens with extreme rightist orientations are more likely to support democracy promotion via military means. Regarding the impact of socio-economic background variables, higher education and working skills are positively associated with democracy promotion in general but make citizens less likely to support democracy promotion via military means. Finally, even if the majority of Europeans do not support democracy promotion via military means, the heterogeneity of country effects suggests that the assumption of a common European identity regarding democracy promotion needs to be refined.
Keywords: 330